Highways and Spatial Location within Cities : Evidence from India - Ghani, Ejaz; Goswami, Arti Grover; Kerr, William R. (Published by Oxford University Press on behalf of the World Bank, 2019)
The authors investigate the impact of the golden quadrilateral (GQ) highway project on the spatial organization and efficiency of manufacturing activity. The GQ project upgraded the quality and width of 3,633 miles of roads in India. The authors use a difference-in-difference estimation strategy to compare non-nodal districts based upon their distance from the highway system. For the organized portion of the manufacturing sector, we find that GQ led to improvements in both urban and rural areas of non-nodal districts located 0 to 10 kilometers from GQ. These higher entry rates and increases in plant productivity are not present in districts 10 to 50 kilometers away. The entry effects are stronger in rural areas of districts, but the differences between urban and rural areas are modest relative to the overall effect. For the unorganized sector, we do not find material effects from the GQ upgrades in either setting. These findings suggest that in the time frames that we can consider the first five to seven years during and after upgrades, the economic effects of major highway projects contribute modestly to the migration of the organized sector out of Indian cities but are unrelated to the increased urbanization of the unorganized sector.